2012
DOI: 10.1128/aem.07056-11
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Redox Balance Increasesl-Valine Production by Corynebacterium glutamicum under Oxygen Deprivation Conditions

Abstract: Production of L-valine under oxygen deprivation conditions by Corynebacterium glutamicum lacking the lactate dehydrogenase gene ldhA and overexpressing the L-valine biosynthesis genes ilvBNCDE was repressed. This was attributed to imbalanced cofactor production and consumption in the overall L-valine synthesis pathway: two moles of NADH was generated and two moles of NADPH was consumed per mole of L-valine produced from one mole of glucose. In order to solve this cofactor imbalance, the coenzyme requirement fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 51 publications
2
100
0
Order By: Relevance
“…Based on previous structural studies and mutational analysis (Brinkmann-Chen et al, 2013;Hasegawa et al, 2012;Rane and Calvo, 1997), we have proposed that cofactor specificity is controlled by up to four amino acid residues in the loop: the first two positions, the antepenultimate position, and the ultimate position, as indicated by red arrows in Figure 1 and labeled for the S. exigua KARI in Figure 2. We searched the expanded sequence alignment for proteins having an acidic residue at any of these four positions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous structural studies and mutational analysis (Brinkmann-Chen et al, 2013;Hasegawa et al, 2012;Rane and Calvo, 1997), we have proposed that cofactor specificity is controlled by up to four amino acid residues in the loop: the first two positions, the antepenultimate position, and the ultimate position, as indicated by red arrows in Figure 1 and labeled for the S. exigua KARI in Figure 2. We searched the expanded sequence alignment for proteins having an acidic residue at any of these four positions.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that the plurality of these putative NADH-utilizing KARIs have acidic residues the first position of the E2DB-loop. Although none of our previous cofactor-specificity reversals required an acidic residue at this position, Hasegawa et al introduced a mutation to glutamate at this position, suggested by comparison with the NADH-dependent dihydrolipoamide dehydrogenases, in an attempt to reverse the cofactor specificity of the C. glutamicum KARI (Hasegawa et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity of acetohydroxy acid synthase (AHAS) was determined in the reaction mixture containing 100 mM potassium phosphate buffer, pH 7.5, 10 mM MgCl 2 , 50 mM pyruvate, 100 M thiamine pyrophosphate (TPP), 100 M flavin adenine dinucleotide (FAD), and the cell-free lysate (ϳ300 g of protein) in a total volume of 500 l at 30°C. The rate of pyruvate consumption was calculated by monitoring the decrease of the absorbance at 333 nm (ε, 17.5 M cm Ϫ1 ) (12). (iii) Transaminase B (IlvE) activity.…”
Section: Methodsmentioning
confidence: 99%
“…In this way a titer of 227 g/L has been achieved with a productivity of 4.7 g/(L h) with yields up to 0.41 g/g. 394 By further eliminating side-reactions, the yield has been increased to 0.57 g/g, at a titer of 150 g/L and a productivity 6.3 g/(L h). …”
Section: L-valinementioning
confidence: 99%